Radar Technology Encyclopedia - Barton, David K.; Leonov, Sergey A. (Boston : Artech House, 1997)
The Encyclopedia explains more than 5 000 terms and concepts related to radar, antenna and microwave technology.
1 CD-ROM : 11,8cm
Keywords: radary; technika radarová; encyklopédie; CD-ROM